A New Beta Chaotic Map with DNA Encoding for Color Image Encryption - Taqi, Ibtisam A.; Hameed, Sarab M. (Iraqi Journal of Science, 2020)
Images hold important information, especially in military and commercial surveillance as well as in industrial inspection and communication. Therefore, the protection of the image from abuse, unauthorized access, and damage became a significant demand. This paper introduces a new Beta chaotic map for encrypting and confusing the color image with Deoxyribonucleic Acid (DNA) sequence. First, the DNA addition operation is used for diffusing each component of the plain image. Then, a new Beta chaotic map is used for shuffling the DNA color image. In addition, two chaotic maps, namely the proposed new Beta and Sine chaotic maps, are used for key generation. Finally, the DNA XOR operation is applied between the generated key and shuffled DNA image to produce the cipher image. The experimental results prove that the proposed method surpassed the other methods in terms of Mean Square Error (MSE), Peak Signal-To-Noise Ratio (PSNR), entropy, and correlation coefficient.